Historiografia, música e decolonialidade: possibilidades no ensino de história no Ceará - Fernandes, Emílio Albuquerque (2023)
This paper proposes, from a given cutout, possibilities of the uses of music as a didactic resource in the classroom for the teaching of history in Ceará. The cutout in question was the investigation/problematization of theses and dissertations on the theme of music as an object of study in Ceará, published in graduate programs in History, between the years 2008 and 2019. We started from a theoretical-methodological debate based on the interlocution between the discussions presented by the sources (based mostly on canonical authors of History) and authors of Post-Colonial Thought, Intersectional Feminisms and Decolonial Turn proposed by this research so that, in this process, we developed laboratories of experimentation of the study of themes of History in Ceará for High School. Thus, in the first part of the chapters we present the authors of the theses and dissertations and their respective theoreticalmethodological inclinations on History and Music, with the aim of identifying the social place of the historiographical operation and revealing the usually hidden epistemic place. In the second part, we indicate a source of each thesis or dissertation, where they assume the condition of a problem-situation, in order to discuss themes concerning the teaching of History in Ceará. In the first chapter we mobilize the concept of intersectionality to identify, through the music of the Belle Époque period, how the oppressions of class, race and gender are correlated, inseparable, and, for this reason, should be studied in combination. In the second chapter we articulate the concept of the modern/colonial world-system to counter the idea of national integration propagated by the estadonovista regime in the music of the Radio Age. We conclude the third chapter by proposing a discussion about the concept of transmodernity and its imbrications in the music of the Military Dictatorship period. As an integral part of this dissertation, we have formulated an Illustrated Guide in the format of a Didactic Support Material for High School History teachers and students.